2020
DOI: 10.3390/ijms21030976
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a 18F-Phenylboronic Acid Radiotracer for Imaging Boron in Maize

Abstract: Boron (B) is an essential plant micronutrient. Deficiencies of B have drastic consequences on plant development leading to crop yield losses and reductions in root and shoot growth. Understanding the molecular and cellular consequences of B deficiency is challenging, partly because of the limited availability of B imaging techniques. In this report we demonstrate the efficacy of using 4-fluorophenylboronic acid (FPBA) as a B imaging agent, which is a derivative of the B deficiency mimic phenylboronic acid (PBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 50 publications
2
20
0
Order By: Relevance
“…In a later study, Cd uptake and translocation in 6 rice cultivars of differing Cd affinity (3 high and 3 low uptake cultivars) was investigated using PETIS and autoradiography ( Figure 8B ). 97 Cd uptake and translocation dynamics were observed between high and low affinity varieties, with high-affinity varieties demonstrating more rapid translocation of Cd from roots to shoots and panicles relative to low-affinity varieties. High-affinity varieties also showed a decrease of Cd in roots after peaking, whereas low-affinity varieties reached a plateau, corresponding with greater export elsewhere in the plant.…”
Section: Positron Imaging For Visualization Of Contaminant Dynamics Imentioning
confidence: 95%
“…In a later study, Cd uptake and translocation in 6 rice cultivars of differing Cd affinity (3 high and 3 low uptake cultivars) was investigated using PETIS and autoradiography ( Figure 8B ). 97 Cd uptake and translocation dynamics were observed between high and low affinity varieties, with high-affinity varieties demonstrating more rapid translocation of Cd from roots to shoots and panicles relative to low-affinity varieties. High-affinity varieties also showed a decrease of Cd in roots after peaking, whereas low-affinity varieties reached a plateau, corresponding with greater export elsewhere in the plant.…”
Section: Positron Imaging For Visualization Of Contaminant Dynamics Imentioning
confidence: 95%
“…The recent application of ablation laser-ICP-MS (inductively coupled plasma mass spectrometry) allowed the development of a mathematical model that enabled the analysis of B distribution along roots of A. thaliana at an extremely high resolution ( Shimotohno et al, 2015 ). To overcome the challenges of B detection in different plant tissues, the fluorinated-18 4-fluorophenylboronic acid radiotracer approach ([18F] FPBA) was recently used ( Housh et al, 2020 ). The images obtained by autoradiography provided insightful information on the patterns of static B location in both root and shoot tissues ( Housh et al, 2020 ), revealing different locations of B distribution.…”
Section: Boron Translocation and Distributionmentioning
confidence: 99%
“…To overcome the challenges of B detection in different plant tissues, the fluorinated-18 4-fluorophenylboronic acid radiotracer approach ([18F] FPBA) was recently used ( Housh et al, 2020 ). The images obtained by autoradiography provided insightful information on the patterns of static B location in both root and shoot tissues ( Housh et al, 2020 ), revealing different locations of B distribution. Briefly, both the root tip and the stretching zone are the ones that exhibited the most intense sign of the tracer with a region between the two devoid of any sign, showing a clear demand for B in these regions ( Housh et al, 2020 ).…”
Section: Boron Translocation and Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advancing knowledge of B deficiency at the molecular and cellular level is a challenge, partly due to the limited availability of B-imaging techniques. Housh et al [13] have demonstrated that radioactively labelled [ 18 F]4-fluorophenylboronic acid (FPBA), which is a derivative of phenylboronic acid (PBA) that mimics B deficiency, accumulates at the root tip, the elongation zone, and the lateral root initiation sites in maize roots, indicating a demand for B in these regions, and also moves to the shoot where it accumulates along the leaf edges. This report supports that radioactively labelled [ 18 F]FPBA can be used to image sites of B demand at the tissue level.…”
mentioning
confidence: 99%